FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN MOTIVASI MASYARAKAT DALAM MENGUNJUNGI POSBINDU PENYAKIT TIDAK MENULAR SAKINAH DI DESA TASIK JUANG KECAMATAN LUBUK BATU JAYA KABUPATEN INDRAGIRI HULU - Fadhli, Rohmi; Miftahunnajib, Miftahunnajib; Amin, Suci (Jurnal Ilmu Keperawatan, 2023)
The increasing prevalence of non-communicable diseases (NCD) and the low motivation of the community to visit NCD posbindu to carry out early examinations, will certainly be a serious threat to health development in the community. NCD has become a major cause of death globally at this time and the incidence of NCD shows that it continues to increase every year. The objective of this study to determine the factors related to people's motivation to visit the Sakinah Non-Communicable Diseases Posbindu in Tasik Juang Village, Lubuk Batu Jaya District, Indragiri Hulu Regency. This type of research is descriptive observational. The number of samples is 180 respondents with simple random sampling technique. The statistical test used is the Chi Square Test. The results of the research on the knowledge factor obtained a p value of 0.048 (p <0.05), it was concluded that there was a relationship between knowledge and community motivation in visiting Posbindu Non-Communicable Diseases, the attitude factor obtained a p value of 0.000 (p <0.05), it was concluded that there was an attitude relationship on community motivation in visiting Non-Communicable Diseases Posbindu, then the education factor obtained a p value of 1.000 (p > 0.05), it was concluded that there was no relationship between education and community motivation in visiting Non-Communicable Diseases Posbindu, then the family support factor obtained a p value of 0.003 ( p <0.05). As a whole it can be concluded that there is a relationship between family support and community motivation in visiting Posbindu Non-Communicable Diseases. It is hoped that health workers can conduct counseling about the functions, benefits and objectives of using Posbindu PTM for the community.